2022
DOI: 10.1038/s41598-022-07124-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered TGFB1 regulated pathways promote accelerated tendon healing in the superhealer MRL/MpJ mouse

Abstract: To better understand the molecular mechanisms of tendon healing, we investigated the Murphy Roth’s Large (MRL) mouse, which is considered a model of mammalian tissue regeneration. We show that compared to C57Bl/6J (C57) mice, injured MRL tendons have reduced fibrotic adhesions and cellular proliferation, with accelerated improvements in biomechanical properties. RNA-seq analysis revealed that differentially expressed genes in the C57 healing tendon at 7 days post injury were functionally linked to fibrosis, im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 62 publications
1
22
1
Order By: Relevance
“…Despite the increased ECM turnover, MRL/MpJ explants experienced the same diminished biomechanical function as B6 explants by 14 days in culture. While previous studies have shown that MRL/MpJ flexor tendons at this age have a lower baseline modulus compared with B6 tendons, 26 we found only a difference in maximum stress at baseline (Supporting Information: Figure ), which could be due to differences in testing protocols. We may need to consider different modes of mechanical evaluation for our studies.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Despite the increased ECM turnover, MRL/MpJ explants experienced the same diminished biomechanical function as B6 explants by 14 days in culture. While previous studies have shown that MRL/MpJ flexor tendons at this age have a lower baseline modulus compared with B6 tendons, 26 we found only a difference in maximum stress at baseline (Supporting Information: Figure ), which could be due to differences in testing protocols. We may need to consider different modes of mechanical evaluation for our studies.…”
Section: Discussioncontrasting
confidence: 85%
“…In other forms of mechanical injury, such as overuse and overload injuries, inflammatory genes including IL-6, TNF-α, IL-1β, and COX-2 were identified to increase in vivo and in vitro. 41,42 26 we found only a difference in maximum stress at baseline (Supporting Information: Figure S7), which could be due to differences in testing protocols. We may need to consider different modes of mechanical evaluation for our studies.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations